The Performative Effects of the European War on Migrants. Masculinities and Femininities at the Moroccan-Spanish Border - Elsa Tyszler (Gender a Výzkum)
This article ethnographically explores how Central and West African masculinities and femininities are shaped and reshaped at the Moroccan-Spanish border in the context of the increased securitisation and politicisation of migrations from the global South to the global North. Apart from the migration regime at the outer border of the European Union, it also examines the role of the humanitarian regime in policing black migrants’ gender identities. It aims to address an important aspect of the mobility experiences and bordering effects that tends to go under-researched. Drawing on long-term fieldwork, which was carried out between 2015 and 2017, it presents detailed ethnographic examples of the construction of masculinities and femininities at the border and asks how these work to help or prevent mobility. Analysis of the intersections of the gender regime and the racialised migratory regime reveals the coloniality of security migration policies.